The chief justiceship of John Marshall, 1801-1835 - Johnson, Herbert Alan. (Columbia, S.C. : University of South Carolina Press, 1997)
Perhaps no individual has exerted a more profound influence on the United States Supreme Court or on the federal Constitution than Chief Justice John Marshall. In this history of the high court during the critical years from 1801 to 1835, Herbert A. Johnson offers a comprehensive portrait of the court's activities and accomplishments under Marshall's leadership. Johnson demonstrates that in addition to staving off political attacks from the Jeffersonian and Jacksonian political parties, the Marshall Court established the supremacy of the federal government in areas of national concern, enunciated the commerce and contract clauses as critical foundations for economic development, and definitively shaped the structure of federalism before the Civil War.
The Chief Justice and his associates -- Politics and Constitution in the Marshall era -- Marshall at the matrix of court leadership -- The Circuit Courts and the projection of federal power -- Federal supremacy and judicial power -- The American common market and property rights -- Fine-tuning the federal common market : private law in the Supreme court -- The United States in the family of nations -- The end of an era.
Includes bibliographical references (pages 293-303) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Marshall, John, -- 1755-1835.; United States. -- Supreme Court -- Biography; États-Unis. -- Supreme Court -- Biographies; Marshall, John, -- 1755-1835; United States. -- Supreme Court; Marshall, John, -- 1755-1835.; United States. -- Supreme Court -- History; Marshall, John (Politiker); Judges -- United States -- Biography; Juges -- États-Unis -- Biographies; LAW -- Government -- Federal; POLITICAL SCIENCE -- Government -- Judicial Branch; LAW -- Legal Services; LAW -- Civil Procedure; BIOGRAPHY & AUTOBIOGRAPHY -- Lawyers & Judges; Judges; United States; Supreme Court (VS); Law - U.S.; Law, Politics & Government; Law - U.S. - General; Biographies; Biographies; Biographies